Study of the pterigidal canal (vidian canal) through images of cone beam computer tomography. - Santana, Fernanda Fritoli Marcondes; Silveira, Marcos Paulo Motta; Diamantino, Pedro Jacy Santos; Fardim, Karolina Aparecida Castilho; Manhães Júnior, Luiz Roberto Coutinho; Costa, André Luiz Ferreira; Saavedra, Guilherme de Siqueira Ferreira Anzaloni; Lopes, Sérgio Lucio Pereira de Castro (Brazilian Dental Science, 2020)
Objective: The aim of this study was to evaluate the pterygoid canal (PC) by Cone Beam Computed Tomography (CBCT), establishing its configuration and proximity with anatomical structures. Material and Methods: We evaluated 398 CBCT exams, all from a public University radiology clinic archive. Four parameters were evaluated: single or double PC, distance between PC and the inferior part of the sphenoid sinus (SS), ratio of PC and SS and the distance between the PC and the foramen rotundum. Results: It was observed that most of the PC of the sample presented simple morphology, the most frequent type of relationship between the PC and the SS on both sides was the close contact with the wall. Among the cases that there were some distances between the PC and the inferior wall of the SS, the mean of this distance did not exceed 3.20 mm, being the left side (3.03 mm) slightly closer than the right (3.20 mm). Finally, the distances between the PC and the corresponding Foramen Rotundum are presented with mean values of 5.87 mm for the right side and 6.31 mm for the left side. Conclusion: CBCT examination is of paramount importance for PC identification; once in the studied sample, the mean values found evidence the close relation between the PC and the SS.KeywordsCone beam computed tomography; Endonasal approach; Vidian canal.